Universitatea vârstei a treia – un răspuns la îmbătrânirea demografică în oraşul Galaţi - Pușcașu, Violeta (Calitatea Vieții, 2016)
This article brings into focus an academic project, in fact a multidimensional one, whose beneficiaries are elder persons. In a small space, the paper addresses two distinct aspects. The first part gives a brief history of the phenomenon of the universities of the third age, history intersecting several social trends. In the second part are analyzed the conditions of the appearances of the structure called the “university of the third age” from the “Lower Danube” University of Galati, with a special focus on the demographic context. In this registry analysis, the article provides a brief overview of the demographic structure of the first series of senior students enrolled at U3A Galati. The purpose of this paper is to introduce into sociological and demographic debate a new theme on the Romanian specificities of U3A phenomenon directly related to the aging population perspectives.